A Chemosensor Based on Gold Nanoparticles and Dithiothreitol (DTT) for Acrylamide Electroanalysis - Shahenvaz Alam; Shine Augustine; Tarun Narayan; John H. T. Luong; Bansi Dhar Malhotra; Sunil K. Khare (Nanomaterials, 2021)
Rapid and simple electroanalysis of acrylamide (ACR) was feasible by a gold electrode modified with gold nanoparticles (AuNPs) and dithiothreitol (DTT) with enhanced detection sensitivity and selectivity. The roughness of bare gold (Au) increased from 0.03 μm to 0.04 μm when it was decorated with AuNPs. The self-assembly between DTT and AuNPs resulted in a surface roughness of 0.09 μm. The DTT oxidation occurred at +0.92 V. The Au/AuNPs/DTT surface exhibited a surface roughness of 0.24 μm after its exposure to ACR with repeated analysis. SEM imaging illustrated the formation of a polymer layer on the Au/AuNPs/DTT surface. Surface plasmon resonance analysis confirmed the presence of AuNPs and DTT on the gold electrode and the binding of ACR to the electrode’s active surface area. The peak area obtained by differential pulse voltammetry was inversely proportional to the ACR concentrations. The limit of detection (LOD) and the limit of quantitation (LOQ) were estimated to be 3.11 × 10−9 M and 1 × 10−8 M, respectively, with wide linearity ranging from 1 × 10−8 M to 1 × 10−3 M. The estimated levels of ACR in potato chips and coffee samples by the sensor were in agreement with those of high-performance liquid chromatography.